EDITORIAL - Vargas, J. V. C. (Revista de Engenharia Térmica, 2002)
This special issue of RETERM – Thermal Engineering is the continuation of the brazilian thermal science community’s effort to bridge the gap between the scientific (academia) and industrial communities. For that, the journal continues to be divided in two main sections: science and technology. The former is directed to publish complete articles that deal with fundamental advances in heat transfer and fluid mechanics, new physical insights, and novel experimental and analytical methods that have great appeal for the industry community, and the latter is designed to comprise informative articles that document modern engineering applications, or general advances in industry. Particularly, in this special issue, the best articles written in English language, presented at the I Brazilian Congress of R&D in Oil and Gas, held in Natal, RN, between November 25th and 28th, 2001, were selected by the Associate Technical Editors of RETERM, according to the scientific criteria of the journal. This way, RETERM specifically addresses the Oil and Natural Gas sector, that has been fomented by the existing great needs and by the existence of CTPETRO – Brazilian National Plan of Science and Technology for the Oil and Natural Gas Sector, that plays a role of crucial importance on fomenting scientific research in Brazil. The institutional support from the Brazilian Society of Mechanical Sciences (ABCM), and from the Brazilian Society of Industrial Machinery and Equipments (ABIMAQ), continues to strengthen our belief in the success of this enterprise. To open a perspective to the maintainance and continuity of RETERM, we invite the readers from the industrial community to contact our staff for subscriptions and publicity in RETERM. For the next issues we continue to welcome technical articles from both the scientific and the industrial communities to either section of RETERM, and contributions to the other sections of the journal, and suggestions for new sections as well. We also welcome response and comments from our readers that will eventually help the success of RETERM.